Assessing Satisfaction With Online Courses: Spanish Version of the Learner Satisfaction Survey - Torrado, Macarena; Blanca, María J. (Frontiers in Psychology, 2022)
The aim of this study was to develop a Spanish version of the Learner Satisfaction Survey (LSS-S) and to analyze its psychometric properties. The questionnaire was administered to a sample of 1,194 university students. Validity evidence based on the instrument's internal structure and on relationships with other variables (personality and motivation) were analyzed. In addition, reliability of test scores and differences by gender and area of knowledge were examined. The results revealed a factor structure with adequate fit indices based on five first-order factors (learner–content, learner–instructor, learner–learner, and learner–technology interactions, and general satisfaction) and one second-order factor (total score for academic satisfaction). Scores on the LSS-S were positively correlated with scores on conscientiousness, intrinsic motivation, and identified regulation, and negatively correlated with scores on neuroticism and amotivation. Although the magnitude of correlations with personality traits was small, those with motivational factors were moderate or strong. Reliability of LSS-S factor scores may be considered satisfactory, with McDonald’s omega ranging from .80 to .86. These results indicate that the LSS-S has satisfactory psychometric properties and that it is an adequate tool for measuring satisfaction with online courses among Spanish learners in higher education.